EFFECTS OF E-COMMERCE ON THE SHARIA HOTELS BRAND AWARENESS IN BANDUNG - Natakusuma, Muchyidin; Arifianti, Ria; Sukoco, Iwan (Advances in Social Sciences Research Journal, 2018)
Sharia has become global, including the development of Sharia Hotels. In addition, the development of internet technology in Indonesia can be seen with the existence of e-commerce which benefits in the form of business convenience because the internet is seen as an advertising media that is cheaper, more efficient and effective. Tight business competition has made brand as an important aspect that can be a benchmark for a company. Sharia hotel owners use e-commerce to build strong brands and make consumers acknowledge that their brands are well received by consumers. This study aims to find out how e-commerce influences brand awareness in Narapati Indah Sharia Boutique Hotel and Convention Bandung. Respondents in this study were sampled using the Structural Equation Modeling (SEM) method that allows testing a series of relatively complex relationships simultaneously. The results showed that respondents’ responses regarding e-commerce and brand awareness at Narapati Indah Sharia Hotel were in the good category. In addition, there is a significant influence between e-commerce on brand awareness in Narapati Indah Sharia Hotel especially through their own website so that to depend on other parties are no longer needed.